(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
Aim: Few researches have been done on the effects of various illnesses on renal function. This key aspect is taken into account for the conduct of our study, and it aids in the continuation of our research and provides a brief overview of the prevalence and predominance of renal failure. The types of renal damage that are more common were described in relation to diseases, age, sex, and social behavior to rule out diseases that cause renal damage. Methodology: At the Suraksha Hospital in Andhra Pradesh’s nephrology department, a nonexperimental prospective observational study was carried out. The duration of the study was roughly 3 years. In the study, 1000 patients were included depending on their diseases, age, sex, and social behavior. Results: Our research identified disorders that affect renal function. Males are more likely to have disorders that affect kidney function, and the 50–70 age bracket is particularly important. Diabetes mellitus (DM) left untreated impairs kidney function. Conclusions: Data show that patients between the ages of 50 and 70 were most affected, whereas those older than 70 were less affected. There were 1000 individuals diagnosed with a renal injury, and out of those, 600 (or 60%) were men and 400 (or 40%) were women. Out of 1000 individuals with renal failure, 625 are located in rural areas, whereas 375 are located in urban areas. DM patients (680, or 68%), hypertension (190, or 19%), urinary tract infection (100, or 10%), and anemia (3%) are the conditions that cause kidney failure.